2016
DOI: 10.1126/sciadv.1600878
|View full text |Cite
|
Sign up to set email alerts
|

The local spiral structure of the Milky Way

Abstract: Researchers have only recently begun to trace the spiral structure of our Galaxy, the Milky Way, and already find surprising results.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
124
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(134 citation statements)
references
References 38 publications
(57 reference statements)
7
124
0
Order By: Relevance
“…The grey background image represents the spatial distribution of the OB stars from Chen et al (2019a). The green, pink and blue dashed lines mark respectively a possible spur 'Lower Sagittarius-Carina Spur', the 'split' found by Lallement et al (2019) and the spur identified by Xu et al (2016). Three black dashed circles mark the positions of three possible hole patterns in the Sagittarius and Perseus Arms identified in Chen et al (2019a).…”
Section: Comparison With Previous Workmentioning
confidence: 97%
See 1 more Smart Citation
“…The grey background image represents the spatial distribution of the OB stars from Chen et al (2019a). The green, pink and blue dashed lines mark respectively a possible spur 'Lower Sagittarius-Carina Spur', the 'split' found by Lallement et al (2019) and the spur identified by Xu et al (2016). Three black dashed circles mark the positions of three possible hole patterns in the Sagittarius and Perseus Arms identified in Chen et al (2019a).…”
Section: Comparison With Previous Workmentioning
confidence: 97%
“…The model line of the Local arm, derived from the OB stars and masers, goes along the upper boundary of Cavity 2, and through the centre of Cavity 1. The lower boundaries of the two cavities seem to be the foreground structure of the spur identified by Xu et al (2016) that connects the Local and the Sagittarius Arms at a pitch angle of " 18˝(the blue dashed line in Fig. 7).…”
Section: The Galactic Spiral Structure As Traced By the Molecular Cloudsmentioning
confidence: 97%
“…The number of star-particles is distributed between the four MSAs and the LA in such a way that the stellar densities of these arms are comparable (e.g. Xu et al 2016). In this way, to each MSA, we attribute a number of 2.56 × 10 7 test particles; to the LA, 1.024 × 10 7 test particles are attributed; and finally, 2.56 × 10 7 test particles are uniformly distributed in the stellar disk background.…”
Section: Initial Conditionsmentioning
confidence: 99%
“…Molecular cloud distances are essential to the study of star formation (McKee & Ostriker 2007;Heyer & Dame 2015;Foster & Brunt 2015;Motte et al 2018) and the Galactic structure (Dame et al 2001;Xu et al 2016Xu et al , 2018a. They are raw materials from which new stars form (Kennicutt & Evans 2012) and are spiral arm tracers (Dame et al 2001;Donovan Meyer et al 2013).…”
Section: Introductionmentioning
confidence: 99%